THE EFFECTIVENESS OF SIMPLER APPLICATION ON VOCABULARY MASTERY OF TENTH GRADE STUDENTS AT SMK MUHAMMADIYAH 3 METRO - Rosi Devis Angelika; Dedy Subandowo; Fitri Palupi Kusumawati (Journal of English Education and Entrepreneurship (JEEP), 2025)
This study aims to determine whether the Simpler application has a significant effect on students’ vocabulary mastery. The research was conducted at SMK Muhammadiyah 3 Metro with two groups: an experimental group that used the Simpler application and a control group that received traditional instruction. The method used in this study was quantitative with a quasi-experimental design. The sample consisted of 76 students, with 38 in each class. Pre-test and post-test data were collected using 30 multiple-choice items focused on vocabulary meaning, usage, synonyms, and antonyms. The average pre-test score of the experimental class was 36.53, which increased to 74.68 after treatment. Meanwhile, the control class showed a smaller improvement from 32.53 to 44.68. The results of the Paired Sample T-Test in the experimental group showed a significance value of < 0.001 (0.000 < 0.05), indicating a significant improvement in vocabulary mastery after using the Simpler application. The Independent Sample T-Test also revealed a significance value of < 0.001, indicating a significant difference in post-test scores between the experimental and control groups. Based on these results, the study concludes that the Simpler application has a positive and significant effect on vocabulary mastery among tenth-grade students at SMK Muhammadiyah 3 Metro.